(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2024)
This article fully describes Uzbekistan’s strategy, personnel, management personnel, political views, political culture, personnel responsibility, leadership responsibility, "democratic state", "legal state", "democratic society", "civil society", leadership activities, responsibilities and responsibilities.